THE DIFFERENCES BETWEEN THE TRANSLATIONS OF MAIMONIDES' GUIDE OF THE PERPLEXED BY FALAQUERA, IBN TIBBON AND AL-HARIZĪ, AND THEIR TEXTUAL AND PHILOSOPHICAL IMPLICATIONS - Shiffman, Yair (Journal of Semitic studies, 1999)
YAIR SHIFFMAN; THE DIFFERENCES BETWEEN THE TRANSLATIONS OF MAIMONIDES' GUIDE OF THE PERPLEXED BY FALAQUERA, IBN TIBBON AND AL-HARIZĪ, AND THEIR TEXTUAL AND PHIL